188 Identification of familial hypercholesterolaemia in patients presenting with premature acute coronary syndrome. (4th June 2021) - Duff, James; Wang, Robin; Graby, John; O'Doherty, Moya
Abstract : Introduction: Familial hypercholesterolaemia (FH) is an underdiagnosed inherited disorder which confers substantial risk of premature cardiovascular disease. Over 90% of those with FH in the UK remain undiagnosed. Its importance was acknowledged in the 2019 NHS long term plan with an aim to identify 25% of FH patients by 2025. Patients with FH may present with an early acute coronary syndrome (ACS) which may represent the first opportunity for diagnosis. Identification of possible FH in this cohort enables specialist follow up, mitigation of risk and investigation of family members via cascade testing. We evaluated local disease burden, assessment of dyslipidaemia and identification of possible FH in a retrospective single centre review. Methods: A retrospective review was conducted of patients presenting with premature ACS to Royal United Hospitals Bath over a 1-year period. Results: We identified 96/573 (17%) patients who presented with ACS under age 60. Although 77/96 (80%) patients had cholesterol measured within 24 hours, only 13/96 (14%) patients had a full lipid profile checked. 14/77 (18%) had a total cholesterol >6.0, of whom 4/14 (29%), 4/14 (29%) and 7/14 (50%) had investigation for hypothyroidism, diabetes or alcohol excess respectively, as secondary causes for hypercholesterolaemia. 5/14 (36%) patients with total cholesterol >6.0 had a family history taken with ages of relatives at onset of CVD; 4/5 (80%) of those asked had a family history of premature CVD. Upon review of high risk cases, 8 were deemed appropriate for referral to lipid clinic, while a further 5 patients may have warranted referral in the presence of a significant family history, but this information was absent in the medical notes. A decision to refer to lipid clinic was documented in 4 patients' notes, although only 2 referrals were received. Conclusion: We identified missed opportunities in the identification of genetic dyslipidaemia (including FH) within a high-risk population. Further investigation through referral to lipid clinic was limited by a number of factors. Limited details of family history, particularly in patients with significant dyslipidaemia, is likely to contribute to under-identification of FH. We identified variable risk stratification and reduced clarity on the accepted threshold for referral to lipid clinic as key barriers to appropriate diagnosis. We propose the introduction of a degree of protocolisation through an 'ACS proforma' and 'lipid clinic referral decision aid' to facilitate appropriate identification, assessment and management of patients with possible FH. Conflict of Interest: None